BRIDGING RISKS AND OPPORTUNITIES: OPERATIONAL STRATEGIES FOR SUSTAINABLE GROWTH VIA ESG MANAGEMENT - Bing Wang; Lokhman Hakim Osman; Mohd Rizal Palil; Nurul Atasha Binti Jamaludin (Operational Research in Engineering Sciences: Theory and Applications)
As a vital component of our nation's economic landscape, enterprises bear a weighty responsibility in advancing the trajectory of high-calibre sustainable growth. However, presently, listed enterprises often harbour risk factors such as neglecting environmental concerns, failing to fulfil social responsibilities, and possessing imperfect corporate governance mechanisms, all of which imperil the sustainability of enterprises. This paper selects coal enterprises as a case study subject to scrutinize the practical implementation of a system. Initially, the necessity of system construction is scrutinized through literature review and theoretical underpinnings. Subsequently, the paper delves into the Environmental, Social, and Governance (ESG) performance and sustainable development within the coal-heavy industry. ESG, as an evolving framework aligned with climate-conscious initiatives, serves as a robust foundation for actualizing the principles of green development and fostering the comprehensive framework of ecological civilization construction. Finally, employing four evaluation methodologies via Abaqus software, the study concludes that an evaluation system centred on ESG perspectives proves to be more precise and dependable compared to previous models. This comprehensive validation underscores the imperative and viability of erecting a sustainable development evaluation system grounded in ESG principles. Furthermore, fortifying environmental regulations stands poised to enhance the market concentration of high-quality enterprises, propel industrial advancement, and mitigate environmental degradation.